Caste, local governance effectiveness, and multidimensional poverty in rural India: some evidences - Amarachi Onyeyirichi Ogbonna; Charles Aaron Adams Ekuban; C. Muralee Krishnan; P. K. Viswanathan (Frontiers in Sociology)
IntroductionThis study explores the relationships between local governance effectiveness, population densities of Scheduled Castes (SC) and Scheduled Tribes (ST), and rural multidimensional poverty in India, using data from the 2011 Indian Census, 2011 Socio-Economic and Caste Census (SECC), 2020 Mission Antyodaya, and 2019/21 National Family and Health Survey (NFHS).MethodsThe research examines how SC/ST population densities and local governance effectiveness are associated with the Multidimensional Poverty Index (MPI) across Indian states through regression and correlation analysis.ResultsThe study’s findings reveal a national, rural MPI of 0.110, with 26% of the rural population experiencing multidimensional poverty. The study’s results also show that a statistically significant negative correlation exists between rural MPI and local governance effectiveness, with a 0.32% reduction in MPI for every 1% improvement in governance effectiveness. Conversely, higher SC and ST population densities are associated with increased MPI, with a 0.14% rise in MPI for each 1% increase in these densities. The study also highlights that ST population density has a stronger association with MPI than SC population density, indicating greater vulnerability to multidimensional poverty in areas with higher ST populations.DiscussionOverall, the study underscores the importance of effective local governance in reducing rural poverty and suggests targeted efforts in areas with high SC and ST densities, particularly ST, to alleviate poverty. It also emphasizes the need for up-to-date data to understand and address rural poverty comprehensively.